"Maybe we should take the legal ways": Citizen engagement with lower state courts in post‐war northern Uganda. Issue 4 (18th November 2022) - Macdonald, Anna; Cooper‐Knock, SJ; Hopwood, Julian
Abstract: Lower state courts are the focus of both international and national access to justice policies and programs but remain understudied in Uganda. Drawing on 3 years of ethnographically informed research on citizen engagement with a busy magistrates' court in post‐war northern Uganda, we show the diverse reasons why citizens appeal to the rule‐of‐law in places where state authority is contested. In a context of limited statehood, against a backdrop of high‐levels of corruption and inefficiency in the judicial system, people turn to lower state courts for normative, pragmatic, and tactical reasons that are not well captured by conventional measures of procedural justice. Our findings extend theory on citizen‐authority relations in a global context, shedding light on contextual meanings of legitimacy, trust, and corruption in places where lower state courts are deeply problematic sites for achieving justice.